The View of the Academy and the Job Market on Teaching Auditing - Hoff, Jhonatan (2017)
The objective of this study was to identify the perception of audit teaching according to the academy and the labor market, based on the evaluation of the importance professionals and teachers grant to the main conceptual and normative aspects of the audit area. In order to achieve the proposed objective, the perception of the teachers responsible for the audit discipline and the auditors working in the labor market was collected through a questionnaire structured in the form of a Likert scale. The research sample comprised all the federal and state universities that offer accounting courses and all the audit companies registered in the database of the Brazilian Securities Commission (CVM). The responses were treated using the non-parametric Mann-Whitney and Spearman’s correlation tests. The results show that, in approximately 75% of the topics raised in this study, the academy tends to correspond to the expectation the market holds about the importance given to such contents within the audit discipline. The main differences are related to Assurance Service, Audit of Non-Profit Entities, Audit of Governmental Agencies, Quality Control and Audit of Information Systems, which do not receive emphasis within the academy, according to the market perspective. The results presented here can be used for teachers to evaluate the disposition of the contents covered within the discipline, considering the relevance attributed by the market.